Nowa klasyczna makroekonomia a polityka stabilizacji gospodarczej w kapitalizmie - Kowalski, Tadeusz (Wydział Prawa i Administracji UAM, 1987)
A considerable deterioration of economic situation in the '70 was accompanied by a gradual rebirth of classical economic conceptions. A clear example of the above is new classical economics formulated in the USA in the '70. That trend calls in question not only the output of Keynesian economics but also its methodological foundations. New classical economics, like monetarism, should be included among general equilibrium theories. The article contains the analysis of theoretical structure of new classical macroeconomics, with the emphasis laid on the key element of that theoretical system, namely the rational expectations hypothesis in J. F. Muth's sense. The article also presents and analyses the new-classical invariance proposition referring to the stabilization policy originating from Keynesian economics. Besides, the article contains the critique of new classical economics and attempts to evaluate the significance of that highly controversial trend for changes occurring in contemporary macroeconomics.
New classical economics and stabilization policy